Laser wavelength modulated pulsed laser ablation for selective and efficient production of graphene quantum dots. Issue 24 (3rd May 2019) - Kang, Sukhyun; Ryu, Jeong Ho; Lee, Byoungsoo; Jung, Kyung Hwan; Shim, Kwang Bo; Han, Hyuksu; Kim, Kang Min
Abstract : Graphene quantum dots (GQDs) and graphene oxide quantum dots (GOQDs) can be selectively produced by wavelength-modulated pulsed laser ablation in liquid (PLAL) method, which can used in different applications such as optoelectronic and biomedical applications, respectively. Abstract : Graphene quantum dots (GQDs) and graphene oxide quantum dots (GOQDs) can be used in different applications such as optoelectronic and biomedical applications, respectively. Hence, the selective synthesis of GQDs and GOQDs is highly desirable but challenging. Here, we present GQDs and GOQDs selectively prepared by an easy and simple pulsed laser ablation in liquid (PLAL) method by controlling the laser wavelength. The obtained GQDs and GOQDs showed a significantly different optoelectronic nature mainly due to the existence of surface oxygen-rich functional groups ( e.g. carboxyl or hydroxy groups). Also, we described a possible mechanism for the formation of oxygen functional groups during the PLAL process based on the Coulomb explosion model, which can give further insight for designing functional carbon materials.